Paul, the Law and Judaism: Stoification of the Jewish Approach to the Law in Paul’s Letter to the Romans - Holtz, Gudrun (Zeitschrift für die neutestamentliche Wissenschaft, 2018)
One of the major issues in Pauline studies of the last decades has been the picture of Judaism painted by Paul especially in his Letter to the Romans. To that end, scholarship first and foremost adduced contemporary Jewish sources without, however, reaching satisfactory results. The present paper, therefore, takes a different approach in that it works out the Stoic influence on Paul’s argumentation. To begin with, the Stoic character of the dilemma of the “I” in Rom 7:14–25, that wills the good, but fails to do so, is demonstrated. Thereupon, it is shown that Paul transfers insights of Stoic psychology not only to the Jewish-Adamitic “I” but also to Israel’s approach to the law that is reached by neither one. Paul in Romans, therefore, can be said to stoify the Jewish approach to the law which especially reflects in the formula “righteousness by works of the law”.